Síntese de acetais e de hemiacetais derivados de terpenos através da reação de hidroformilação catalisada por complexos de ródio modificados - Marina Caneschi de Freitas (2014)
Rhodium-catalyzed tandem hydroformylation/acetalization of -pinene, -pinene, 2-carene and 3-carene was studied in ethanol solutions in the presence of PPh3 or P(O-o-tBuPh)3 as auxiliary ligands. -Pinene, the only substrate containing exocyclic double bond, gave corresponding aldehyde and acetal in excellent combined yields in both systems. On the other hand, -pinene, 2-carene, 3-carene, which contain sterically encumbered trisubstituted endocyclic double bonds, showed good reactivity only in the Rh/P(O-o-tBuPh)3 systems. This ligand presents a large cone angle and a strong -acidity. The processes were performed in environmentally friendly ethanol as the solvent, in the absence of acid co-catalysts and the mixtures of fragrance acetals and aldehydes were obtained in nearly quantitative yields. Rhodium-catalyzed hydroformylation of sesquiterpene nerolidol was studied in toluene andethanol solutions in the presence of PPh3 or P(O-o-tBuPh)3 ligands. In toluene, the reaction gave with high selectivity a cyclic hemiacetal, which formally arises from the intramolecular cyclization of the primarily formed hydroxy aldehyde. In ethanol, the reaction gave a corresponding cyclic acetal in excellent yields even without additional acid co-catalysts.